Gymnodinium catenatum strains isolated from the portuguese coast: physiological and genetic characterization - Silva, Teresa Lopes da, 1973- (2014)
Tese de mestrado. Biologia (Biologia Molecular e Genética). Universidade de Lisboa, Faculdade de Ciências, 2013